Evaluation of Inclusive Education in University: Gaps in Program Implementation - Putranto, Sumbaji (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
Inclusive education is the implementation of equality in education. To support the implementation of inclusive education, the Mathematics Education Study Program at UIN Sunan Kalijaga makes inclusive one of its core values. This is a discrepancy model evaluation developed by Provus. Data was carried out through questionnaires, interviews, documentation, and observation. Based on the results, it can be concluded that the implementation of inclusive education is in the moderate category. This can be seen from the results of the questionnaire which shows the percentage reaching an average of 68.77%. In detail, the results for each indicator are 1) Vision, mission, goals, and strategy standards reached the very good category; 2) Graduate competency standards reached the moderate category; 3) Learning process standards reached the moderate category; 4) Learning assessment standards reached the moderate category; 5) Student Standards reached the moderate category; 6) Standards for lecturers and education personnel reached the moderate category; 7) Learning infrastructure standards reach the moderate category; 8) Learning financing standards reach the moderate category; and 9) Learning management standards reach the moderate category. Based on the existing findings, some of the main recommendations for the implementation of inclusive education in the Mathematics Education Study Program are to develop individualized learning programs that appropriate the needs of students with special needs, training for lecturers and student volunteers for the implementation of learning in inclusive classes, and the appointment of a coordinator in the implementation of inclusive education in the mathematics education study program.